Long-term deep brain stimulation of the ventral anterior limb of the internal capsule for treatment-resistant depression. Issue 2 (4th December 2019) - van der Wal, Junus M.; Bergfeld, Isidoor O.; Lok, Anja; Mantione, Mariska; Figee, Martijn; Notten, Peter; Beute, Guus; Horst, Ferdinand; van den Munckhof, Pepijn; Schuurman, P. Rick; Denys, Damiaan
Abstract : Objective: Deep brain stimulation (DBS) reduces depressive symptoms in approximately 40%–60% of patients with treatment-resistant depression (TRD), but data on long-term efficacy and safety are scarce. Our objective was to assess the efficacy and safety of DBS targeted at the ventral anterior limb of the internal capsule (vALIC) in 25 patients with TRD during a 1-year, open-label, maintenance period, which followed a 1-year optimisation period. Methods: Depression severity was measured using the 17-item Hamilton Depression Rating Scale (HAM-D-17), Montgomery-Asberg Depression Rating Scale (MADRS) and self-reported Inventory of Depressive Symptomatology (IDS-SR). Primary outcomes were response rate (≥50% HAM-D-17 score reduction) after the maintenance phase, approximately 2 years after DBS surgery, and changes in depression scores and occurrence of adverse events during the maintenance phase. Results: Of 25 operated patients, 21 entered and 18 completed the maintenance phase. After the maintenance phase, eight patients were classified as responder (observed response rate: 44.4%; intention-to-treat: 32.0%). During the maintenance phase, HAM-D-17 and MADRS scores did not change, but the mean IDS-SR score decreased from 38.8 (95% CI 31.2 to 46.5) to 35.0 (95% CI 26.1 to 43.8) (p=0.008). Non-responders after optimisation did not improve during the maintenance phase. Four non-DBS-related serious adverse events occurred, including one suicide attempt. Conclusions: vALIC DBS for TRD showed continued efficacy 2 years after surgery, with symptoms remaining stable after optimisation as rated by clinicians and with patient ratings improving. This supports DBS as a viable treatment option for patients with TRD. Trial registration number: NTR2118.